THE EFFECTS OF PLAYING METHOD ON THE ACTIVITIES OF CHILDREN AGED 4-5 YEARS OLD IN TK MUTIARA BANGSA SURABAYA - Made Ayu Anggreni; Dirganto . (Universitas Muhammadiyah Ponorogo, 2018)
This research aimed to examine the effects of playing method on the activeness of learning during the learning process, the reciprocal questions between early childhood and teachers. The research was conducted in the neighborhood of TK Mutiara Bangsa Surabaya with a population of 36 children and a sample of 20 children aged 4-5 years old. The sample technique was carried out through purposive sampling based on considerations that were already known by the researcher and the characteristics of the children that were known beforehand. The data collection of this research used the observation test instrument which was analyzed using statistical analysis with 2 designs: Pre-test and post-test and without the comparison/control group. The results of this research indicated that learning activeness after treatment or treatment with playing method, there was an effect of learning activeness with an average score of -9.50000. Also, based on the results of the t-test testing, it was known that the value of -26.456 with a significance of 0.000 (p lt;0.05) which means that there was a very significant effect between the method of playing on the learning activeness children aged 4-5 years old in TK Mutiara Bangsa Surabaya. There was a positive effect between playing method on learning activities of children aged 4-5 years old. Playing is the part of the child#39;s soul without any compulsion. The active child does anything because of great curiosity, information, experience experimenting from playing and the teacher as facilitator. Through playing, it will be easier to optimize all aspects of child’s development, creating the next generation who are ready for changing times. Playground can be used for early childhood learning.